Attaining the 2030 sustainable development goal of good health and well-being - Birdthistle, Naomi; Hales, Rob (Family businesses on a mission, 2023)
The ebook edition of this title is Open Access and freely available to read online. Attaining the 2030 Sustainable Development Goal of Good Health and Well-Being focuses on Sustainable Development Goal number three (SDG#3): prioritising the emotional and physical health of humans around the world. Examining family businesses in Germany, Malaysia, Mexico, and Australia, each case study presents a unique perspective from their respective country, analysing how SDG#3 translates into ensuring healthy lives and promoting well-being for all. The case studies presented generate insights and key takeaways into the role of family businesses in fostering safety and equality in healthcare systems and infrastructure across the globe. The United Nations' (UN) Sustainable Development Goals (SDGs) are 17 Goals pledged by 193 nations in 2015 which would help engender an improved, fairer, and more sustainable world - one in which 'no one is left behind'. The SDGs are a call to action, to develop innovative solutions to the most complex, societal, and environmental global challenges. In Family Businesses on a Mission, series editors Naomi Birdthistle and Rob Hales bring together international case studies to illustrate how family businesses can attain the UN 2030 SDGs. Accessible to those working in the field beyond academia - such as family business practitioners, family business owners, government and policymakers, members of NGOs, business associations and philanthropic centres - this book series equally appeals to those with a general interest in entrepreneurship and business.